2016
DOI: 10.1007/s00103-016-2339-2
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitliche Situation und Versorgung unbegleiteter minderjähriger Flüchtlinge – eine Näherung anhand qualitativer und quantitativer Forschung in der Stadt Bielefeld

Abstract: Unaccompanied minor refugees are children or adolescents below the age of 18 years who are not accompanied by their parents. International studies show that unaccompanied minor refugees represent a special risk group. Currently, empirical study results about the health status of unaccompanied minor refugees barely exist for Germany. Therefore, the goal of this article is an assessment of the health status and health care of unaccompanied minor refugees in Bielefeld, Germany. For this purpose, two qualitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…Female URM, for example, are at a higher risk of sexual exploitation and abuse during the flight. 18 Other pathways relate to gender differences in coping styles or attitudes towards mental health and illness. 17…”
Section: Introductionmentioning
confidence: 99%
“…Female URM, for example, are at a higher risk of sexual exploitation and abuse during the flight. 18 Other pathways relate to gender differences in coping styles or attitudes towards mental health and illness. 17…”
Section: Introductionmentioning
confidence: 99%
“…6 11 12 For instance, studies from Germany have found that psychosocial care (PSC) for UMRs is provisionally provided by emergency and refugee relief 6 and in so-called clearing centres 7 12 and is legally administered by youth and social welfare services. 12 Health services research has identified a multitude of legal, cultural and language barriers in access to and utilisation of PSC for (adult) refugees, 11 13 14 but UMRs and their PSC processes have scarcely been studied so far. In light of the current situation of young refugees on the Greek islands and the efforts of the non-governmental organisations that are advocating for their admission to Germany so that they may be cared for, this research project is of high importance and topicality.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most quantitative 7 12 17 18 and qualitative 6 12 17 18 studies on UMRs have documented either epidemiological 12 17 18 data or access to psychosocial healthcare services based on expert assessments and have not included lay perspectives. 6 7 12 17 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An abundance of data show that many refugees suffer from diseases such as the common cold, respiratory infections, diabetes etc., and especially from psychiatric disorders [ 8 ], [ 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ]. However, regarding infections, refugees and migrants are not considered a threat to the general population; instead, they are to be perceived as a highly vulnerable group [ 22 ].…”
Section: Introductionmentioning
confidence: 99%